THE EFFECT OF VARIOUS DESENSITIZING AGENT APPLICATION ON IN-OFFICE BLEACHING ON THE NUMBER OF FIBROBLASTS - Apriliyani, Nunik Rahayu; Mulyawati, Ema; Kristanti, Yulita (Odonto : Dental Journal, 2021)
Background: Reactive Oxygen Species (ROS) released from hydrogen peroxide causes inflammation of the pulp. Remineralization action by fluoride-containing desensitizing agent (Casein Phosphopeptides-Amorphous Calcium Fluoride Phosphate/CPP-ACFP) occluding dentinal tubule, thereby minimizing the penetration of hydrogen peroxide into the pulp and affect the number of fibroblasts. The aim of this study was to determine the effect of fluoride-containing desensitizing agent (CPP-ACFP) application: before, after, and before-after in-office bleaching techniques using 40% hydrogen peroxide on the number of fibroblasts.Method: Twenty-eight maxillary molar teeth were divided into 4 groups, Control Group (bleaching treatment), Group I (CPP-ACFP application before bleaching), Group II (CPP-ACFP application after bleaching), and Group III (CPP-ACFP application before and after bleaching). Rats were sacrificed 5 days after and histological preparations were stained with HE. Fibroblasts counting was performed using a 1000x magnification light microscope.Result: ANOVA test showed that there were significant mean differences in the number of fibroblasts among the groups. The LSD test showed that there were statistically significant differences in almost all of the compared groups except between the Control Group and Group II.Conclusion: The number of fibroblasts in the pulp of rats applied CPP-ACFP before and after in-office bleaching was less than applied CPP-ACFP before or after in-office bleaching.